Produção de energia elétrica nas regiões norte e nordeste e impactos econômicos: uma análise a partir do dendê na região norte e solar na região nordeste - Nunes, Jacqueline Lopes (Universidade do Vale do Rio dos Sinos, 2012)
The access to the electric power supply is an essential component for the economic and social development of a country. However its generation has not been enough in order to supply the North and Northeast regions of Brazil, which difficulty the operations of the main necessities of a citizen, like hospitals and schools. Nevertheless, these regions have ideal climatic conditions to palm oil plantation, in North region, and solar radiation, in Northeast region, to enhance the generation of electricity. This dissertation analyses the potential of the electric power supply in the North and Northeast of Brazil and also check the socioeconomics impacts derived from them. The methodology is documental, using bibliographic research. The dissertation concludes that the palm oil, in the North region, and solar, in Northeast, could provide fiscal and economic benefits, as well as to electric power supply for these regions. The palm oil could provide not only employment and income to population, but also could supply the demand of energy required by the Isolated Systems. Regarding the solar energy, it would provide not only employment and income, but also business opportunities to the region, since it provides possibilities to develop new commercial activities. Furthermore, this energy source could be determinant for the energy supply of places with low electrification and could supply this region in 2030.
Keywords: Dendê; Energia solar; Norte; Nordeste; Impactos econômicos; Palm oil; Solar energy; North; Northeast; Economic impacts; ACCNPQ::Ciências Sociais Aplicadas::Economia